The Influence of Work Environment and Work Motivation on Employee Performance with Organizational Citizenship Behavior (OCB) as a Mediating Variable - I Putu Aditya Endra PRATAMA; I Wayan Gde SARMAWA; Ni Made WAHYUNI (International Journal of Environmental, Sustainability, and Social Science, 2025)
In today’s competitive era of globalization, the quality of human resources has become a critical factor in determining a company’s sustainability and performance. This study aims to examine the effect of the work environment and work motivation on employee performance, with Organizational Citizenship Behavior (OCB) serving as a mediating variable at CV. Mahaprima Textile. The research adopts a quantitative approach with an explanatory design, utilizing a census sampling technique by distributing structured questionnaires to all employees, totaling 68 respondents. Data were analyzed using the Partial Least Squares (PLS) method. The findings reveal that while the work environment has a positive but statistically insignificant effect on employee performance, it exerts a positive and significant influence on OCB. Similarly, work motivation shows a positive yet insignificant effect on performance, but has a significant positive impact on OCB. Furthermore, OCB has a significant effect on employee performance and is found to fully mediate the relationship between the work environment and employee performance, as well as partially mediate the relationship between work motivation and performance. These results underscore the pivotal role of OCB in enhancing the impact of the work environment and work motivation on employee performance.